Peningkatan kemampuan menganalisis unsur intrinsik cerpen melalui pembelajaran inkuiri pada siswa kelas IX SMP - Ki Ahmad Saleh Amirullah (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
The purpose of this study is to get a more real picture of the application of inquiry learning in improving the ability to analyze the intrinsic elements of short stories for students in grade IX of junior high school. This study took the subjects of class IX students and students as many as 36 people. Data collection was carried out by essay test method. In the initial test the average score of students was 4.00, in the first cycle the average score of students was 5.12, in the second cycle the average value of the students was 5.72, in the third cycle the average value of students was 7.44. So it can be concluded that inquiry learning can improve the ability to analyze the intrinsic elements of short stories for students in grade IX of junior high school.